Effect of COL5A1, GDF5, and PPARA genes on a movement screen and neuromuscular performance in adolescent team sport athletes: erratum - Stastny, P.; Lehnert, M.; Croix, M. D. S.; Petr, M.; Svoboda, Z.; Maixnerova, E.; Varekova, R.; Botek, M.; Petrek, M.; Kocourkova, L.; Cieszczyk, P. (The Journal of Strength and Conditioning Research, 2021)
In the article, "Effect of COL5A1, GDF5, and PPARA Genes on a Movement Screen and Neuromuscular Performance in Adolescent Team Sport Athletes"(1), which appears in Volume 33, Issue 8 of The Journal of Strength and Conditioning Research, the Acknowledgements section should read "This study has been supported by the GACR grant No. 16-13750S, by Charles University grant UNCE/HUM/032 and by grant IGA_PU_LF 2018_015/2019_009."